CUTTING METHODS AND VOLUMES OF TIMBER HARVESTING IN MOUNTAIN FORESTS IN UKRAINIAN CARPATHIANS - Parpan, V. I.; Hudyma, V. D.; Parpan, Т. V. (Forestry and Forest Melioration, 2018)
Introduction The area of mountain forests of the Ukrainian Carpathians reaches 1 million 457 thousand hectares, 70.6 % of which are the forests of the State Forest Resources Agency of Ukraine. Forest exploitation is carried out depending on the natural and economic conditions, location, species composition of the forests and the functioning role. A limited and special regime of forest exploitation is applied in forests of following special purposes: environment-oriented, recreational, and protective, which account for 17 %, 9 % and 28 % of the area of mountain forests, respectively. Exploitable forests occupy 46 % of the area. Intensive use of forests in Carpathian Mountains continues over 300 years. Therefore, the stands were at least 1–2 times completely felled followed by subsequent natural and anthropogenic restoration, including the establishment of pure spruce plantations, which massively dying now. Forests were also impacted by large-scale exogenous natural hazards (winds, diseases, pests), which in some periods increased the volume of forest exploitation. Under the influence of these factors, a modern age structure of the forest cover was formed. It indicates that during the 80–100-year period in the Carpathians, about 80 % of the forest-covered area was felled. Logging was carried out mainly by clear felling in all functional categories of forests. Young, middle-aged and mature forest stands are conditionally even-aged and conditionally uneven-aged in types of age structure. Mature and overmature stands are mostly climax-type coenoses with uneven-aged structure. Such stands were preserved in small areas in hard-to-reach places. Now they are identified as old-aged forests and virgin forests. The aim of this study was to reveal the current volumes of forest use in the mountain forests of the Carpathians, namely the ratio of methods and types of felling for main use, cutting for the shaping of landscape and recreational felling, and the volume of the formation of cuttings within the functional categories. Materials and Methods Materials for analyzing the volumes of modern forest exploitation were data from reports on actual cuttings in mountain forests of all forestry enterprises of the Carpathian region, subordinated to the State Forest Resources Agency of Ukraine. The analysis was based on data from the area and volume of felled timber, using the mean value for three years (2013–2015). Results In the mountain forests of the Ukrainian Carpathians, forest exploitation is annually carried out on an area of about 38.3 thousand ha and 2,824 thousand m3 of merchantable wood is harvested. Most of the timber harvesting (1.6 million m3) is accounted for commercial forests, the fourth part, to protective forests. The final felling accounts for 40 % and sanitation felling is 51 % of the annual volume of timber harvesting. As for the methods of final felling, 52 % of timber is harvested by clear-felling, 38 % by the last attempt of gradual felling, 9 % by the first attempt of gradual felling, and about 1% by the voluntary-selective felling. Comparison of modern data with materials from the 1990s demonstrates that the proportion of methods of felling for main use has changed insignificantly during the last 25 years. Clear-cutting remains the main method. About 8.5 thousand hectares of cut areas occur in the Carpathians annually, of which 67.9 % are cut areas of spruce, 21.7 % of beech, and 8.5% of fir. About 58 % of cut areas are formed in the commercial forests, and 42 % are restricted to forests with a limited and special regime of use. In terms of the impact on the water regulation functions of forests, the methods of cutting are ranged as follows: selective felling is the most environmentally effective, then gradual felling, and then continuous felling. Conclusions The main method of timber harvesting in the mountain forests of the Ukrainian Carpathians remains clear-cutting. Forestry logging (including final clear-cutting, last attempt of gradual felling, clear sanitation and regeneration felling) harvests 83 % of timber. The percentage of clear sanitation felling in the total volume of timber harvesting is 43 %. About 8.5 thousand hectares of cut areas are formed in the Carpathians annually, of which 58 % are in commercial forests, 27 % in protective forests, 9 % in recreational forests, and 6% in environment-oriented forests. According to the methods of cutting, half of the cut areas are for clear sanitary felling and 20 % for main-use clear-cutting. Voluntary-selective felling of main use harvests less than 1 % of timber. Hydrological effects of clear cuts are twice as large as that of gradual felling and 10 times as large as of selective felling. Therefore, the introduction of a selective management system is an urgent task for mountain forestry. 1 Figs., 7 Tables, 18 Refs.